Improving Access to Savings through Mobile Money: Experimental Evidence from African Smallholder Farmers - Catia Batista; Pedro C. Vicente (Institute of Labor Economics (IZA), 2019)
Investment in improved agricultural inputs is infrequent for smallholder farmers in Africa. One barrier may be limited access to formal savings. This is the first study to use a randomized controlled trial to evaluate the impact of using mobile money as a tool to promote agricultural investment. For this purpose, we designed and conducted a field experiment with a sample of smallholder farmers in rural Mozambique. This sample included a set of primary farmers and their closest farming friends. We work with two cross-randomized interventions. The first treatment gave access to a remunerated mobile savings account. The second treatment targeted closest farming friends and gave them access to the exact same interventions as their primary farmer counterparts. We find that the remunerated mobile savings account raised mobile savings, but only while interest was being paid. It also increased agricultural investment in fertilizer, although there was no change in investment in other complementary inputs that were not directly targeted by the intervention, unlike fertilizer. These results suggest that fertilizer salience in the remunerated savings treatment may have been important to focus farmers' (limited) attention on saving some of their harvest proceeds, rather than farmers being financially constrained by a lack of alternative ways to save. Our results also suggest that the network intervention where farming friends had access to non-remunerated mobile money accounts decreased incentives to save and invest in agricultural inputs, likely due to network free-riding because of lower transfer costs within the network. Overall this research shows that tailored mobile money products can be used effectively to improve modern agricultural technology adoption in countries with very low agricultural productivity like Mozambique.
Keywords: D14; D85; Q12; Q14; 330; mobile money; social networks; savings and agricultural investment; randomized field experiment; Mozambique; Africa